Share

Get Access to:

- Ask & get answers from experts & other users
- Play Quiz and test your skills
- Free Download eBooks, Notes, Templates, etc.
- Study Materials
- Latest Articles

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

Please briefly explain why you feel this question should be reported.

Please briefly explain why you feel this answer should be reported.

Please briefly explain why you feel this user should be reported.

The quadratic formula is:

x = (-b Â± sqrt(b^2 – 4ac)) / (2a)

where a, b, and c are coefficients of the quadratic equation ax^2 + bx + c = 0.

In the given equation, we have:

a = 6 b = 5 c = 3

Substituting these values into the quadratic formula, we get:

x = (-5 Â± sqrt(5^2 – 4(6)(3))) / (2(6)) x = (-5 Â± sqrt(25 – 72)) / 12 x = (-5 Â± sqrt(-47)) / 12

Since the square root of a negative number is not a real number, this equation has no real solutions.

Therefore, the values of x are complex numbers:

x = (-5 + iâˆš47) / 12 or x = (-5 – iâˆš47) / 12, where i is the imaginary unit.